The industrial policies of 14 member countries - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1971)
The purpose of this volume is to give readers a general view of the industrial policies of fourteen countries as of the period 1969/1970: Germany, Belgium, Canada, Denmark, Spain, France, Ireland, Italy, Norway, the Netherlands, Portugal, Sweden, Switzerland and Finland.
Includes bibliographical references.
ne 11/06/2018
Loans
Keywords: Industrial policy